2021
DOI: 10.1021/acs.organomet.1c00256
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Route to 1,1′,2,2′-Tetraiodoferrocene That Avoids Isomerization and the Electrochemistry of Some Tetrahaloferrocenes

Abstract: An efficient synthesis of 1,1′,2,2′-tetraiodoferrocene is described that uses 1,1′,2,2′-tetrakis­(tri-n-butylstannyl)­ferrocene as a key intermediate in its synthesis. In an attempt to examine the stepwise mechanism, the reaction of the tetratin-substituted ferrocene 1,1′,2,2′-tetrakis­(tri-n-butylstannyl)­ferrocene with iodine was monitored by 1H NMR and a series of coexisting intermediate compounds such as 1,1′-bis­(tri-n-butylstannyl)-2,2′-diodoferrocene were observed. The crystal structure of 1,1′,2,2′-tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…From both CV and DPV experiments, the E1/2 and Ep values obtained for 5 are close to that predicted by the computational model (0.76 V). As commonly observed for other substituted ferrocenes,43,[54][55][56][57] a linear relationship exists between the redox potential of the organometallic and the sum of Hammett constant σp 58 according to the equation E1/2 = 2.0791 ∑σp -0.92 (R 2 = 0.9924; plot SI1).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…From both CV and DPV experiments, the E1/2 and Ep values obtained for 5 are close to that predicted by the computational model (0.76 V). As commonly observed for other substituted ferrocenes,43,[54][55][56][57] a linear relationship exists between the redox potential of the organometallic and the sum of Hammett constant σp 58 according to the equation E1/2 = 2.0791 ∑σp -0.92 (R 2 = 0.9924; plot SI1).…”
supporting
confidence: 52%
“…Plots of the available E1/2 vs. ∑R for mono-to pentahomohalogenoferrocenes are given the SI. 43,57 The data show that the redox potential of the four (F, Cl, Br, I) mono-, the four 1,1'-homodihalogenoferrocenes fall into distinct clusters, and two pentahaloferrocenes Fe( 5 -C5Cl5)Cp and Fe( 5 -C5F5)Cp fall into a third one (Plot SI2). As discussed by Long, the data within each cluster are non-linear with electronegativity of the halogen, but reflect more subtle combination of factors including orbital re-ordering, changes in hybridization and frontier orbital composition, electrostatic repulsion between metal and Cp ring orbitals as well as through-space interactions between the iron center and halogen atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of this lack of effect remains unclear as this substituent usually raises the E 1/2 value by 0.13 V. 140,143 In the ferrocene series, the E 1/2 value of substituted ferrocenes usually correlates with the sum of the Hammett values σ p . 141,144–147 However, when we evaluated a related relationship for the 2-substituted ferrocenesulfonyl fluorides, we found that the fluorinated derivative 3e falls out the expected trend. This probably results from the strong resonance effect of fluorine which counterbalances its inductive effect.…”
Section: Resultsmentioning
confidence: 91%
“…Any attempts to produce longer C14-Br14 and C24-Br24 'bonds' via the use of restraints met with failure. It should be noted at this point that the crystal structure of 1,1 0 ,2,4-tetraiodoferrocene showed a similar disorder and an apparent 'bond shortening', which the authors were able to resolve (Evans et al, 2021).…”
Section: Refinementmentioning
confidence: 85%